1994
DOI: 10.1002/jlb.56.6.817
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the production of Fos and Jun by influenza virus-exposed T cells

Abstract: This study investigated age-related T cell responses after in vitro exposure to influenza A virus. Mononuclear leukocytes from young or elderly persons were sham-exposed or exposed to influenza virus for 1, 24, and 72 h. Immunofluorescent staining and flow cytometric analysis were then used to detect T cells producing the transcriptional regulating proteins Fos and Jun. Fewer virus-exposed cells from elderly donors stained for Fos and Jun at each data point compared with cells from young donors. Flow cytometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Two studies utilized purified T cells to evaluate age-related changes in IFNyproduction. One study evaluated T-cell production in response to stimulation with live influenza virus and showed a 2-fold, but non-significant decrease, in the number of IFNy producing T-cells when stimulated with live influenza virus as measured by immunofluorescent intracellular cytokine staining [42]. These results are consistent with the two studies of influenza stimulation of PBMC in which both studies showed a decrease, but only one was significant.…”
Section: Ifn7supporting
confidence: 83%
“…Two studies utilized purified T cells to evaluate age-related changes in IFNyproduction. One study evaluated T-cell production in response to stimulation with live influenza virus and showed a 2-fold, but non-significant decrease, in the number of IFNy producing T-cells when stimulated with live influenza virus as measured by immunofluorescent intracellular cytokine staining [42]. These results are consistent with the two studies of influenza stimulation of PBMC in which both studies showed a decrease, but only one was significant.…”
Section: Ifn7supporting
confidence: 83%
“…92demonstrating decreased cjun mRNA but normal c-fos mRNA responses to PHA in T cells from elderly donors. Moreover, fewer lymphocytes from elderly donors exposed to influenza virus in vitro expressed fos and jun compared to cells of younger donors, possibly as a reflection of compromized activation of antiviral responses (105). Amongst the transcription factors of known importance for IL 2 production, CD3-stimulated induction of NF-kappa B was also found to be decreased in old mice (106) and humans (107).…”
Section: Alterations In Signal Transductionmentioning
confidence: 99%
“…These data are consistent with those of Song et al (177) demonstrating decreased c-jun mRNA but normal c-fos mRNA responses to PHA in T cells from elderly donors. Moreover, fewer lymphocytes from elderly donors exposed to influenza virus in vitro expressed fos and jun compared to cells of younger donors, possibly as a reflection of compromised activation of anti-viral responses (188). In Fischer rats, the age-associated decrease in IL 2 mRNA and protein correlates with a decreasing ability of nuclear extracts of freshly isolated T cells to bind an oligonucleotide representing the transcription factor NF-AT (189), suggesting differences in transcriptional regulation in young and old cells.…”
Section: Cytokine Production and Responsementioning
confidence: 99%